Social Entrepreneurship | UC Berkeley (UC Berkeley Sutardja Center, 2022)
What is Social Entrepreneurship? Social Entrepreneurship is an entrepreneurial venture with a strong community-oriented mission: examples include micro-financing or technologies for clean water in rural areas. The field has grown very quickly over the past few years, and has merged with the technology sector incredibly, with most social ventures considered unpractical if they do not…